Effects of a glyphosate-based herbicide on the uterus of adult ovariectomized rats - Varayoud, Jorgelina Guadalupe (2017)
Glyphosate is the active ingredient of several herbicide formulations. Different reports suggest that glyphosate-based herbicides (GBHs) may act as endocrine disruptors. We evaluated the potential estrogenic effects of a GBH formulation using the uterotrophic assay. Adult ovariectomized rats were sc injected for 3 consecutive days with: saline solution (vehicle control), 2.10−5 g E2/kg/day (uterotrophic dose; UE2), 2.10−7 g E2/kg/day (nonuterotrophic dose; NUE2), or 0.5, 5, or 50 mg GBH/kg/day of the. Twenty-four hours after the last injection, the uterus was removed and weighed and processed for histopathology and mRNA extraction. Epithelial cell proliferation and height and expression of estrogen-responsive genes were evaluated (estrogen receptors, ERα and ERβ; progesterone receptor, PR; complement 3, C3). Uterine weight and epithelial proliferation were not affected by GBH. However, the luminal epithelial cell height increased at GBH0.5. ERα mRNA was downregulated by all GBH doses and E2 groups, whereas PR and C3 mRNA were diminished by GBH0.5. GBH5-, GBH50-, and UE2-treated rats showed downregulated ERα protein expression in luminal epithelial cells, while the receptor was upregulated in the stroma. GBH upregulated ERβ (GBH0.5–50) and PR (GBH5) expressions in glandular epithelial cells, similar effect to that of NUE2 group. These results indicate that, although the uterine weight was not affected, GBH modulates the expression of estrogen-sensitive genes.